The identification of watermilfoil, discovery of hybrid watermilfoil, and their implications for aquatic plant management in the Clark Fork River, Western MT, USA. Issue 1 (10th December 2021) - Madsen, John D.; Wersal, Ryan M.; Schmid, Samuel A.; Thum, Ryan A.; Welch, Mark E.; Phuntumart, Vipaporn
Abstract: Eurasian watermilfoil ( Myriophyllum spicatum ) is an invasive submersed macrophyte that has infested many waters in North America since its introduction. Eurasian watermilfoil has the ability to alter the structure and function of the ecosystems that it invades. Eurasian watermilfoil was first surveyed in the Clark Fork River, MT in 2008, alongside the native northern watermilfoil ( Myriophyllum sibiricum ). Three reservoirs (Cabinet Gorge, Noxon Rapids and Thompson Falls) on the lower Clark Fork River had entire lake surveys conducted using the point intercept method. Morphological data from these surveys showed that only Eurasian watermilfoil and northern watermilfoil were present during the time of the surveys in 2008. The results of the morphological identification were supported by molecular identification at three different laboratories. In 2015, a genetic survey of watermilfoil species was conducted on the Noxon Rapids Reservoir and found that hybrid watermilfoil ( Myriophyllum spicatum × sibiricum ) was present. This hybridization event poses a number of issues for aquatic plant management. Hybrid watermilfoil is much more difficult to identify morphologically than its parent types. The hybrid is also more invasive and may be differentially susceptible to some herbicides than the parental type Eurasian watermilfoil.